Effectiveness of Unconventional Monetary Policy in the Euro Area: An Assessment Based on a Literature Survey - Salomon Fiedler; Isabel Hanisch; Nils Jannsen; Maik Wolters (Credit and Capital Markets – Kredit und Kapital, 2017)
The ECB has adopted a variety of unconventional monetary policy measures since the Global Financial Crisis. In this paper, we assess the effectiveness of unconventional monetary policy measures based on a review of the empirical literature and on theoretical considerations. Empirical assessments exhibit a high uncertainty since it is very difficult to identify the definite effects of unconventional monetary policy and historical evidence is scarce. Therefore, the estimated effects vary considerably across studies. Overall, the available evidence for the euro area suggests that unconventional measures had significant effects on financial market variables, e. g., they reduced long-term interest rates or stimulated asset prices. Unconventional monetary policy also seems to have stimulated economic activity (GDP and consumer prices) to some extent. The available evidence suggests that unconventional monetary policy had the largest effects at the height of the Global Financial Crisis and the sovereign debt crises on economic activity in the euro area. Afterwards, the effects on economic activity most likely have been rather low. Moreover, the risks associated with unconventional monetary policy measures are expected to increase while the effects on economic activity decrease the longer they are in place. – – Analyse und Bewertung der Wirksamkeit unkonventioneller geldpolitischer Maßnahmen im Euroraum: Ein Literaturüberblick Seit Beginn der Finanzkrise hat die EZB eine Vielzahl unkonventioneller geldpolitischer Maßnahmen ergriffen. In dieser Arbeit untersuchen wir die Wirksamkeit dieser Maßnahmen anhand eines empirischen Literaturüberblicks und theoretischer Betrachtungen. Die Ergebnisse empirischer Studien unterliegen aufgrund von Identifikationsproblemen bei der Analyse der Effekte unkonventioneller Geldpolitik und den wenigen verfügbaren historischen Daten hoher Unsicherheit. Dementsprechend variieren die Schätzergebnisse stark zwischen den einzelnen Studien. Insgesamt deuten die vorliegenden Ergebnisse darauf hin, dass die unkonventionellen geldpolitischen Maßnahmen signifikante Auswirkungen auf die Finanzmärkte hatten und z. B. zu einem Sinken der langfristigen Zinssätze und einem Anstieg von Vermögenspreisen geführt haben. Weiterhin gibt es Anzeichen dafür, dass die unkonventionellen geldpolitischen Maßnahmen zu einem gewissen Grad positive Effekte auf die Wirtschaftsaktivität (das BIP und die Konsumentenpreise) haben. Zudem deuten die vorliegenden Ergebnisse darauf hin, dass die Maßnahmen die stärkste Wirksamkeit während der Höhepunkte der globalen Finanzkrise und der europäischen Staatschuldenkrise erreicht haben. Im Laufe der Zeit hat die Wirksamkeit in Bezug auf die Wirtschaftsaktivität eher abgenommen. Ferner erhöhen sich die Risiken unkonventioneller geldpolitischer Maßnahmen mit zunehmender Dauer.
Keywords: E65; E52; E58; 330; Unconventional monetary policy measures; balance sheet measures; Forward guidance; effectiveness; financial markets; real economy; transmission channels